An evaluation of road accident factors using fermatean fuzzy Stepwise Weight Assesment Ratio Analysis (SWARA) / Muhammad Aiman Johari - Johari, Muhammad Aiman (2025)
This study investigates the factors contributing to road accidents in the Melaka Tengah district, utilizing the Fermatean Fuzzy Stepwise Weight Assessment Ratio Analysis (SWARA) methodology. The focus is on factors influenced by human behavior, including over-speeding, fatigue, drunk driving, use of mobile phones, disobeying traffic lights, changing lanes without signaling, and failure to maintain a safe gap. Data were collected from six experts, comprising police officers from the traffic department, through interviews and questionnaires to evaluate and rank the seven critical road accident factors.